2017
DOI: 10.3389/fpsyg.2017.01396
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Cues Embedded in the Kinematics of Human Motion Are Detected in Form-from-Motion Areas of the Visual System and in Motor-Related Areas

Abstract: The present study investigated the cortical areas engaged in the perception of graviceptive information embedded in biological motion (BM). To this end, functional magnetic resonance imaging was used to assess the cortical areas active during the observation of human movements performed under normogravity and microgravity (parabolic flight). Movements were defined by motion cues alone using point-light displays. We found that gravity modulated the activation of a restricted set of regions of the network subten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Internal models related to gravity may be thought of as a form of physics engine used to make accurate predictions of how objects will act in a gravitational environment (Battaglia et al, 2013;Ullman et al, 2017). Neuroimaging and brain stimulation studies have identified the insular cortex and temporoparietal junction as likely candidates for housing the internal model of gravity (Isnard et al, 2004;Indovina et al, 2005;Bosco et al, 2008;Maffei et al, 2015), with additional gravity-dependent activity in visual and motor areas (Cignetti et al, 2017) as well as the cerebellum (Laurens et al, 2013;MacNeilage and Glasauer, 2018;Mackrous et al, 2019). Investigations on movement and perception of gravity have revealed a reliance on an assumption of normal Earth gravity (McIntyre et al, 2001), but this assumption can be altered Frontiers in Physiology frontiersin.org with time and training (Crevecoeur et al, 2009;Torok et al, 2019), suggesting that the internal model of gravity is adaptable.…”
Section: Neuromechanical Adaptation In the Nervous Systemmentioning
confidence: 99%
“…Internal models related to gravity may be thought of as a form of physics engine used to make accurate predictions of how objects will act in a gravitational environment (Battaglia et al, 2013;Ullman et al, 2017). Neuroimaging and brain stimulation studies have identified the insular cortex and temporoparietal junction as likely candidates for housing the internal model of gravity (Isnard et al, 2004;Indovina et al, 2005;Bosco et al, 2008;Maffei et al, 2015), with additional gravity-dependent activity in visual and motor areas (Cignetti et al, 2017) as well as the cerebellum (Laurens et al, 2013;MacNeilage and Glasauer, 2018;Mackrous et al, 2019). Investigations on movement and perception of gravity have revealed a reliance on an assumption of normal Earth gravity (McIntyre et al, 2001), but this assumption can be altered Frontiers in Physiology frontiersin.org with time and training (Crevecoeur et al, 2009;Torok et al, 2019), suggesting that the internal model of gravity is adaptable.…”
Section: Neuromechanical Adaptation In the Nervous Systemmentioning
confidence: 99%